A composite vignette: xylazine, infectious complications and the importance of community-based drug checking services - Liam John; Nathaniel Flint; Francesca Piccolo; Katherine Hill; Marion Anderson; Brian Townsend; Michael Fletcher; Cole Altomare-Jarczyk; Kristen Silvia; Traci Green; Dasan Thamattoor; Jean Bessette; et al. (Therapeutic Advances in Infectious Disease)
Here we describe a composite vignette of a patient who developed necrotic wounds and systemic infection after reported exposure to xylazine, a veterinary anesthetic found as an adulterant in the unregulated drug supply. While exposure to xylazine-containing compounds via the use of fentanyl is not a new phenomenon, xylazine’s prevalence in overdose deaths has escalated, and its geographic distribution has expanded to include rural areas such as Maine. We use this composite vignette to highlight: (1) the growing number of overdoses in Maine where xylazine was found in combination with fentanyl, (2) the potential severe, infection-related complications of xylazine exposure, and (3) describe novel harm reduction strategies that utilize community- and laboratory-based drug checking technology.